Paul Hoffmann and the cutaneous silent period test - Fustes, Otto Jesus Hernández; Kay, Cláudia Suemi Kamoi; Lorenzoni, Paulo José; Ducci, Renata Dal-Prá; Rodrigues, Paula Raquel do Vale Pascoal; Scola, Rosana Herminia (Arquivos de Neuro-Psiquiatria, 2025)
We herein present aspects of the biography of Professor Paul Hoffmann, covering his main works, mainly the article describing the cutaneous silent period, a new technique when it was published in 1922, with a review of its importance, its role in clinical neurophysiology, and its clinical application.
Keywords: Cutaneous Silent Period; Neurology; Neurophysiology